The Effect of Principal’s Leadership and Work Environment on Teacher’s Performance - Hernawati, Hernawati; Widayatsih, Tri; Wahidy, Achmad (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this research is to identify and describe: (1) the influence of the principal's leadership on teacher performance; (2) the influence of the work environment on teacher performance; and (3) the combined influence of the principal's leadership and the work environment on teacher performance. This study was carried out in Kayuagung District Public High School in Ogan Komering Ilir Regency, with 59 teachers as participants. Techniques for collecting data include surveys or questionnaires, recordkeeping, and interviews. Construction and content validity are used in the validity test. Cronbach's Alpha is used in the dependability test. Analysis precondition tests include the normality, linearity, multicollinearity, and heteroscedasticity tests. Simple linear regression and multiple linear regression approaches were used to evaluate the data. The findings revealed that: (1) the principal's leadership has an impact on teacher performance; (2) the work environment has an impact on teacher performance; and (3) the school principal's leadership and the work environment have an impact on teacher performance.